Luminescence and electrical properties of Eu‐modified Bi0.5Na0.5TiO3 multifunctional ceramics. Issue 9 (7th March 2019) - Lun, Mengmeng; Wang, Wei; Xing, Zhifeng; Wan, Zhong; Wu, Wanying; Song, Hanzhao; Wang, Yinzhen; Li, Wei; Chu, Benli; He, Qinyu
Abstract: The Eu 3+ ‐modified Bi0.5 Na0.5 TiO3 (BNT) ceramics have been fabricated by the solid‐state reaction method. The impact of Eu 3+ doping on the structure, photoluminescence, and electrical properties has been studied by XRD, SEM, PL spectra, and LCR meter. X‐ray diffraction analysis reveals that the crystal structure of the samples is well matched with the trigonal perovskite, and the optimal temperature of presintering is 880°C. The Eu 3+ ‐doped BNT ceramics show excellent red fluorescence at 614 nm corresponding to the 5 D0 → 7 F2 transition of Eu 3+ under 466 nm excitation and relatively long fluorescence lifetime. The BNT‐0.02Eu ceramic density is up to 5.68 g/cm 3 and the relative density is up to 94.6% with sintering temperature 1075°C. The piezoelectric constant (d33 ) of samples has been significantly improved up to 110 pC/N by Eu 3+ doping. The BNT‐0.03Eu ceramic presintered at 880°C and sintered at 1050°C has good dielectric properties and excellent luminescence properties. Eu 3+ ‐doped BNT ceramics make it potential applications for novel integrated electro‐optical and multifunctional devices.